Enhanced Performance of DTC-DSC of Induction Machine utilizing 3-Level Cascade H-Bridge Multilevel Inverter - Ravin Nair a/l P.Nagarajan; Auzani Jidin; Tole Sutikno; Md.Nazri Othman; Mohd Luqman bin Mohd Jamil; M. Zharif Rifqi Zuber Ahmadi (IAES Indonesia Section, 2014)
The paper presents a new 3L DTC-DSC scheme for induction motor driver by selecting proper voltage vector for medium and high application. In conventional 3L DTC two different voltage vectors are assigned to vary flux for low speed, medium speed and high speed applications. This paper purposes a scheme for low speed operation of induction machines by using the same technique as conventional 3L DTC. However for a high speed operation, only a single voltage vector is applied thus resulting dodecagon flux locus.The new scheme also improves the torque capabalities and the dynamic of torque performances.